(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to analyses of semantic-structural features of proverbs and sayings in modern Uzbek and English languages. Moreover comparative typology and lingua-cognitive aspects of proverbs and sayings are mentioned.